PHP modernization approach generating KDM models from PHP legacy code - Amine Moutaouakkil; Samir Mbarki (Institute of Advanced Engineering and Science, 2020)
With the rise of new web technologies such as web 2.0, Jquery, Bootstrap. Modernizing legacy web systems to benefit from the advantages of the new technologies is more and more relevant. The migration of a system from an environment to another is a time and effort consuming process, it involves a complete rewrite of the application adapted to the target platform. To realize this migration in an automated and standardized way, many approaches have tried to define standardized engineering processes. Architecture Driven Modernization (ADM) defines an approach to standardize and automate the reengineering process. We defined an ADM approach to represent PHP web applications in the highest level of abstraction models. To do this, we have used software artifacts as a entry point . This paper describes the extraction process, which permits discovering and understanding of the legacy system. And generate models to represent the system in an abstract way.